2007
DOI: 10.1063/1.2767227
|View full text |Cite
|
Sign up to set email alerts
|

Formation and characterization of carbon nanowires

Abstract: This article reports on the formation and electronic characteristics of conducting carbon nanowires produced by swift heavy ion irradiation of a fullerene thin film. This study shows that it is possible to create arrays of carbon nanowires, which are perfectly parallel to each other and perpendicular to the substrate. As-deposited fullerene films exhibit poor field emission characteristics with breakdown fields as high as 51 V / m, whereas low dose ion irradiated fullerene film produces a threshold field as lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 23 publications
(23 reference statements)
3
22
1
Order By: Relevance
“…In fact, we have reported a number of nanowires from various synthetic polymers and biomacromolecules [5][6][7][8][9]. In addition, it was demonstrated that nanowires were developed from small molecules based on π-conjugated molecules [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, we have reported a number of nanowires from various synthetic polymers and biomacromolecules [5][6][7][8][9]. In addition, it was demonstrated that nanowires were developed from small molecules based on π-conjugated molecules [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…They reported that tracks should be formed above a threshold (dE/dx) e value of about 3-4 keV/nm. Although there have been a number of studies on damage of fullerene by ion beam [3,4,[7][8][9][10] indicating the possible formation of ion tracks, no direct evidence of tracks in fullerenes by microscopy techniques has been reported. The damage process under the dense electronic excitations in such a complicated systems needs to be investigated in more details.…”
Section: Introductionmentioning
confidence: 99%
“…The controlled conducting nano wire patterns formation in films by ion beam has been demonstrated [3,4]. Phase transformation of fullerene by ion beam has been a topic of fundamental research interests.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the CNWs have not been regarded as promising structures for nanoelectronic devices because of their poor electrical conductivity about 10 À1 cm À1 [6], though metallic CNWs were reported recently [7,8]. So far, concerns regarding nanowire thin films, having potential for diverse applications such as sensors and also large scale applications, have looked tremendous interest [9,10]. Therefore, it is worth conducting further systematic studies on CNWs.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, a-CNW thin films were developed [9,10] and considered as potential building blocks for future miniaturised devices. However, the fabrications of these thin films with multiple-way junctions have not been reported so far.…”
Section: Introductionmentioning
confidence: 99%